2016
DOI: 10.5194/bg-13-2511-2016
|View full text |Cite
|
Sign up to set email alerts
|

Looking beyond stratification: a model-based analysis of the biological drivers of oxygen deficiency in the North Sea

Abstract: Abstract. Low oxygen conditions, often referred to as oxygen deficiency, occur regularly in the North Sea, a temperate European shelf sea. Stratification represents a major process regulating the seasonal dynamics of bottom oxygen, yet, lowest oxygen conditions in the North Sea do not occur in the regions of strongest stratification. This suggests that stratification is an important prerequisite for oxygen deficiency, but that the complex interaction between hydrodynamics and the biological processes drives it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 64 publications
(97 reference statements)
2
80
1
Order By: Relevance
“…Other studies (OSPAR, 2010;Painting et al, 2013) showed that N inputs from the large Dutch and German rivers are the major contributors to TN in the coastal southern and southeastern North Sea, respectively, while those from the rivers at the British North Sea coast extend far east into the off-shore southern North Sea. This, together with the findings by Große et al (2016), suggests that these N sources have a strong influence on the O 2 dynamics in the southern and southeastern North Sea.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…Other studies (OSPAR, 2010;Painting et al, 2013) showed that N inputs from the large Dutch and German rivers are the major contributors to TN in the coastal southern and southeastern North Sea, respectively, while those from the rivers at the British North Sea coast extend far east into the off-shore southern North Sea. This, together with the findings by Große et al (2016), suggests that these N sources have a strong influence on the O 2 dynamics in the southern and southeastern North Sea.…”
Section: Introductionsupporting
confidence: 65%
“…Große et al (2016) showed that the model system captures the main features of observed O 2 concentrations in the North Sea. Therefore, only the simulated volume transports are validated and spatial distributions of TN from selected sources are presented and compared to earlier TBNT studies.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations